Determinant Factors of Logistic Information Technology (LIT) Adoption by Logistic Service Providers ( LSPs) in Malaysia : A Review - Salim, Hanisah Mat; T., Ramayah; Karia, Noorliza (School of Social Sciences, USM, 2017)
Purpose- This paper aims to identify the determinant factors of Logistic Information Technology (LIT)Adoption by Logistic Service Providers (LSPs) in Malaysia. Many LSPs in Malaysia however have not realized the need to employ technology in their operations and haven’t implemented information technology and aligned their strategies with the changes in technology. Technology has been used as competitive tool to again competitive edge against competition and in most instances redesigning the sales process. With these developments, efficiency in service delivery has been key in pushing many organisations towards implementation of computer systems. Logistic Information Technology is where LSPs implement various logistics systems is one of the technologies implemented towards improving service delivery. The purpose of this study is to understand factors affecting the implementation of LIT adoption by LSPs in Malaysia. This research was guided by TOE model in identifying factors determining LIT adoption by LSPs in Malaysia. PLS-SEM is used to analyse the relationship of each construct using the structural equation modeling. This research concludes a need for LSPs to further understand the importance of LIT and how it can shape their operations towards improving service delivery.